Probe into BB1M abuse: Cops form task force to investigate fraudulent - Daniel, Steven; Majid, Embun (The Star, 2012)
KUALA LUMPUR : Bukit Aman has set up a task force to investigate the fraudulent sale of the 1Malaysia book vouchers (BB1M).